(3hUhd GdCNjGQ Edi CUhd GdCNHGQs - (3HgGA GdOjf GdYGedj , eMeO Hf MSjf Hf YHO GdUeO GdMGQKj GdgePGfj, HgGA GdOjf,J (B1031 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGJM GdGZdGb hHYO ajbhd abjQ QHg deG cGf GdJabg ai ReGffG gPG hGLHkG Ydi cd Gdecdajf s
(3BNQgG (B:s
(3hSeYJ eMeO jbhd hbO GUWdMhG GjVkG Ydi EKHGJ GTjGA ai GdcJGHI Ohf GdbQGAI eKd cJGHI GdhGh hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B242s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs